The presence of Haemoproteus spp in wild birds in Greece - THEODORIDIS (Ι. ΘΕΟΔΩΡΙΔΗΣ) Y.; ALEXAKIS (ΑΛΕΞΑΚΗΣ Α.) A.; MATARA (ΜΑΤΑΡΑ Χ.) Ch. (Journal of the Hellenic Veterinary Medical Society, 2018)
Blood smears from 541 birds of 11 different species, killed in 4 continuous hunting periods (1977-1980), at Macedonian region, were examined. One hundred and six were found to be infected with the protozoon Haemoproteus. A higher infection rate was observed in the orphean warblers (Sylvia hortensis 58,3%) and, in descending order, in the turtle-doves Streptopelia turtur 33,3%), the partridges (Perdix per dix 33,3%), the goldfinches (Carduelis carduelis 30,4%), the greenfinche orioles (Carduelis chloriis 29,5%), the house sparrows (Passer domesticus 27,6%), the blackbirds (Turdus merula 15%), the quails (Coturnix coturnix 7,62%), and the CettPs warblers (Cettia cetti 7,1%). The parasite was not found in blood smears from song thrushes (Turdus philomelos) and reavings (Turdus iliacus).